Evaluation of longan (Dimocarpus longan) peel powder as fruit by-product additive in Nile tilapia (Oreochromis niloticus) feed: Effects on growth, immunity, and immune-antioxidant gene expressions - Supreya Wannavijit; Piyatida Outama; Chinh Le Xuan; Camilla Maria Fontana; Marina Paolucci; Md Afsar Ahmed Sumon; Ehab El-Haroun; Hien Van Doan (Heliyon)
The study, herein, investigated the effects of the inclusion of longan peel (LP) powder in the diet of Nile Tilapia (Oreochromis niloticus), focusing on comparative evaluations of growth performance, immunity, and immune-antioxidant related gene expressions. For this purpose, a total of 300 healthy fish (average initial weight: 13.70 ± 0.06 g) were randomly distributed into five experimental treatment groups: 0 g kg−1 (LP0), 10 g kg−1 (LP10), 20 g kg−1 (LP20), 40 g kg−1 (LP40), and 80 g kg−1 (LP80), all in triplicate, for 60 days. The results indicated that dietary supplementation with LP exhibited a significant influence (P < 0.05) in weight gain (WG), specific growth rate (SGR) and provided a better feed conversion ratio (FCR) in contrast to the control group (0 g kg−1 LP). Moreover, skin mucus and serum immune parameters (lysozyme and peroxidase activity) were significantly higher (P < 0.05) in fish fed with different LP concentrations at both 4 and 8 weeks. Similarly, analysis of mRNA transcripts of immune (IL-1, IL-8, and LBP) and antioxidant (GSTa, GPX, and GSR) gene expressions showed a significant upregulation (P < 0.05) in LP-fed diet groups compared to the control group. Based on the polynomial regression analysis the inclusion of LP at 46–49 g kg−1 can be used effectively in Nile tilapia diets for improving the growth, immunity, and immune-antioxidant gene expressions. All in all, our results prove that LP is a very promising feed supplement for the Nile tilapia in the context of aquaculture.